Структурно-семантические особенности новых фразеологических единств немецкого и английского языков - Егошина, Т.Е.; Лагутина, А. (Культура народов Причерноморья, 2013)
Данная работа посвящена исследованию структурно-семантических особенностей новых
фразеологических единств немецкого и английского языков в сравнении. Среди анализируемых моделей
образования ФЕ были выделены наиболее продуктивные, а также были отмечены модели, которые
являются неактивными в образовании новых ФЕ на данном временном этапе.
Кроме того, в работе представлена классификация тематической аттракции новообразованных ФЕ
английского и немецкого языков. Статья построена на традиционных методах исследования.
Ключевые слова: фразеология, фразеологическое единство, структура, семантика, тематическая
аттракция. Дана робота присвячена дослідженню структурно-семантичних особливостей нових
фразеологічних єдностей німецької та англійської мов в порівнянні. Серед аналізованих моделей
утворювання ФЄ були виділені найбільш продуктивні, а також були відзначені моделі, які є
неактивними в утворюванні нових ФЄ на даний період.
Крім того, у роботі представлено класифікація тематичної атракції новоутворених ФЄ англійської та
німецької мов. Дослідження використовує традиційні методи дослідження фразеологічних єдностей.
Ключові слова: фразеологія, фразеологічна єдність, структура, семантика, тематична атракція The work under consideration is devoted to the analysis of structural-semantic peculiarities of newlyformed
phraseological units of the German and English languages taken in comparison. Among analyzed
patterns of formation of phraseological units the most productive patterns were singled out. In the German
language these are the following patterns: V+S; V+Präp+S; V+S+Präp+S; Adj+S; S+Präp+S;
Adj(Part)+Konj+Adj(Part); Adj+Konj+S; Adj+Kong+S. Other patterns are non-productive at the moment. In
the English language these are the following most productive patterns: N+N; Adj+N. Other patterns are nonproductive
at the moment as well. The article is based on traditional methods.
It should be mentioned that all the newly-formed phraseological units were grouped according to their thematic
attraction. Eleven groups were formed: 1. A man. 2. External characteristics of a person. 3. The nature of the
man.
4. Intellectual abilities. 5. Interpersonal relationships. 6. Social status. 7. Physical condition; emotional state. 8.
Actions. Types of activities. 9. Things. 10. Qualities. 11. Appearance.
Key words: phraseology, phraseological units, structure, semantics, thematic attraction